2017
DOI: 10.1038/nature22041
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of cytokinesis forces via E-cadherin dilution and actomyosin flows

Abstract: During epithelial cytokinesis, the remodelling of adhesive cell-cell contacts between the dividing cell and its neighbours has profound implications for the integrity, arrangement and morphogenesis of proliferative tissues. In both vertebrates and invertebrates, this remodelling requires the activity of non-muscle myosin II (MyoII) in the interphasic cells neighbouring the dividing cell. However, the mechanisms that coordinate cytokinesis and MyoII activity in the neighbours are unknown. Here we show that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 51 publications
8
141
0
Order By: Relevance
“…Fig. 4E, arrows), as was previously observed in the pupal notum (Pinheiro et al, 2017). NB invagination and the cell rearrangements that drive germband extension overlap with the onset of mitosis of some of the later mitotic domains.…”
Section: Canoe Is Critical For Cells To Retain Columnar Architecture supporting
confidence: 78%
“…Fig. 4E, arrows), as was previously observed in the pupal notum (Pinheiro et al, 2017). NB invagination and the cell rearrangements that drive germband extension overlap with the onset of mitosis of some of the later mitotic domains.…”
Section: Canoe Is Critical For Cells To Retain Columnar Architecture supporting
confidence: 78%
“…Studies have also shown that AJ proteins are downregulated in the cancer cells[15], suggesting that cancer cells do not require attachment. Thus, cancer cells, which gradually lose AJ protein expression[51], may not be as sensitive to ECM adhesivity as normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Heeding these lessons should enable the creation of genetic tools for an unprecedented range of experimental approaches. This study (see [19] for parent plasmid) Fig. 1 IO@CTV-Pax-Cherry (Targeting Vector for Insertion at C-terminus) Variants:…”
Section: Resultsmentioning
confidence: 99%